2018
DOI: 10.1016/j.watres.2017.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and activated carbon act as promising amendments for promoting the microbial debromination of tetrabromobisphenol A

Abstract: The increasing occurrence of tetrabromobisphenol A (TBBPA) in the environment is raising questions about its potential environmental health impacts as it has been shown to cause various deleterious effects in humans. The fact that the highest concentrations of TBBPA have been reported in wastewater sludge is concerning as effluent discharge and biosolids land application are likely a route by which TBBPA can be further disbursed to the environment. Our objectives in this study were to evaluate the effect of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…In the present study, by the end of the 133-day experiment, of the 51.5 μmol of TBBPA added (cumulative amount), 91.2±1.2 % and 86.3±2.2% had been transformed to BPA, in the metabolic and co-metabolic TBBPA-spiked reactors, respectively (Fig 1). Based on this observation, as well as the published results from two previous studies (Lefèvre et al, 2018;Lefevre et al, 2016), we concluded that microbial reductive debromination was the major process responsible for TBBPA transformation in our reactors. Unlike what was observed in our previous similar study in which acetate addition delayed the onset of TBBPA degradation by approximately two weeks (Lefevre et al, 2016), in the present study, TBBPA transformation started nearly immediately in both reactors with no acclimation period ( Fig.…”
Section: Tbbpa Degradationsupporting
confidence: 85%
See 4 more Smart Citations
“…In the present study, by the end of the 133-day experiment, of the 51.5 μmol of TBBPA added (cumulative amount), 91.2±1.2 % and 86.3±2.2% had been transformed to BPA, in the metabolic and co-metabolic TBBPA-spiked reactors, respectively (Fig 1). Based on this observation, as well as the published results from two previous studies (Lefèvre et al, 2018;Lefevre et al, 2016), we concluded that microbial reductive debromination was the major process responsible for TBBPA transformation in our reactors. Unlike what was observed in our previous similar study in which acetate addition delayed the onset of TBBPA degradation by approximately two weeks (Lefevre et al, 2016), in the present study, TBBPA transformation started nearly immediately in both reactors with no acclimation period ( Fig.…”
Section: Tbbpa Degradationsupporting
confidence: 85%
“…Four bench scale anaerobic sludge reactors were assembled and operated as previously described (Lefèvre et al, 2018), and filled with 1.5 L of activated sludge (4.1±0.7 g/L of suspended solids) collected the same day at the North Durham WWTP (NC, US). The cometabolic set of reactors (i.e., reactor #1 and #2) received 1 g of sodium acetate trihydrate (5 mM final concentration), while the metabolic set (i.e., reactor #3 and #4) did not receive any additional source of carbon.…”
Section: Reactor Operation and Samplingmentioning
confidence: 99%
See 3 more Smart Citations